Solvent based switching of photophysical properties of transition metal complexes - Alsindi, Wassim Zuhair (2007)
The work presented in this Thesis describes the modular design and spectroscopic study of polynuclear systems based on ruthenium (II) and rhenium (I) complexes. A combination of UV/vis, luminescence and TRIR spectroscopies, electrochemistry, spectroelectrochemistry and conformational analysis have been employed to understand the electronic structure of the ground and excited states of these compounds. Chapter I gives an introductory background to this Thesis. An overview of transition metal photophysics and excited states, and the typical spectroscopic and electrochemical techniques used in their study is presented. Previous studies of the ground and excited state properties of the complexes [Ru(bpy)3]2+ and [ReCl(CO)3bpy)] which are used as supramolecular building blocks in this Thesis are presented and a number of relevant studies of supramolecular systems are described. Chapter 2 contains a study extending the known family of [Ru(CN)4(NN)]2- complexes and describes their unique advantages over [Ru(bpy)3]2+. The results obtained are discussed alongside previous studies. This completes the introduction of the molecular building blocks used in Chapters 3 and 4. Chapter 3 details a study of through-space PEnT in bimetallic systems constructed from the complexes introduced in Chapters I and 2, bridged by a saturated alkyl linker between bpy ligands on either metal. This Chapter demonstrates the solvent-switchable nature of the direction and gradient of PEnT, using ps-TRIR spectroscopy to directly probe these processes in real time. Chapter 4 describes a study of bimetallic systems bridged by conjugated the ligand 2,2'- bipyrimidine. Monometallic, homobimetallic and heterobimetallic systems are studied and questions arising from limitations of previous studies are addressed. In particular ps-TRIR spectroscopy gives new insight into the numerous ultrafast processes occurring. Chapter 5 summarises the achievements of this Thesis and suggests promising directions for extending this work in the future. Chapter 6 describes the experimental and theoretical techniques used in this Thesis.